Hypofibrinogenaemia and hypocalcaemia in adult trauma patients receiving pre‐hospital packed red blood cell transfusions: Potential for supplementary pre‐hospital therapeutic interventions. (27th October 2021) - Bodnar, Daniel; Stevens, Zoe; Williams, Sue; Handy, Michael; Rashford, Steven; Brown, Nathan J
Abstract: Objective: To report the arrival ionised calcium (iCa) and fibrinogen concentrations in trauma patients treated with packed red blood cells by the road‐based high‐acuity response units of a metropolitan ambulance service. Methods: A retrospective review of trauma patients treated with packed red blood cells by high‐acuity response units between January 2012 and December 2016. Patients were identified from databases at southeast Queensland adult trauma centres, Pathology Queensland Central Transfusion Laboratory, Gold Coast University Hospital blood bank and the Queensland Ambulance Service. Patient characteristics, results of laboratory tests within 30 min of ED arrival were analysed. Results: A total of 164 cases were analysed. The median injury severity score was 33.5 (interquartile range 22–41), with blunt trauma the commonest mechanism of injury ( n = 128, 78.0%). Fifty‐eight of the 117 patients (24.4%) with fibrinogen measured had a fibrinogen concentration ≤1.5 g/L; 79 of the 123 patients (64.2%) with an international normalised ratio (INR) measurement had an INR >1.2; 97 of 148 patients (63.8%) with an iCa measured, had an iCa below the Pathology Queensland reference range of 1.15–1.32 mmol/L. Arrival fibrinogen concentration ≤1.5 g/L and arrival iCa ≤1.00 were associated with in‐hospital mortality with odds ratio 11.90 (95% confidence interval 4.50–31.65) and odds ratio 4.97 (95% confidence interval 1.42–17.47), respectively. Conclusions: Hypocalcaemia and hypofibrinogenaemia on ED arrival were common in this cohort. Future work should evaluate whether outcomes improve by correction of these deficits during the pre‐hospital phase of trauma care. Abstract : In trauma patients that received pre‐hospital packed red blood cell transfusion, 24.4% had a fibrinogen concentration ≤ 1.5 g/L on arrival and 63.8% had an iCa <1.15 mmol/L. Arrival fibrinogen concentration ≤ 1.5g/L and arrival iCa ≤ 1.00 mmol/L were associated with in‐hospital mortality with odds ratio = 11.90 and odds ratio = 4.97, respectively. Future work should evaluate whether outcomes improve by correction of these deficits during the pre‐hospital phase of trauma care.